Analisis Kemampuan Peserta Didik Menyelesaikan Soal Cerita Berdasarkan Indikator Polya - Yunarti, Yunarti; Roesdiana, Lessa (Universitas Dr. Soetomo, 2021)
Abstract Human life will never be undone from various problems which are required us to solve them precisely and quickly without any mistakes. Mathematics, which is one of the compulsory subjects in school, take an important role in human life as a process of problem-solving learning. The most experiencing problem for students is the lack of ability to solve mathematics problems in terms of stories. Thus, the research aimed to find out how students’ ability level to solve mathematics problems in terms of story based on Polya indicator. The researcher used the qualitative approach method with descriptive analysis. The subjects of the research are 30 students of 9th-grade students at Telagasari 1 Junior High School who were picked randomly. Based on the Polya indicator, the result of data analysis showed that 23, 33% of students were sufficient to understand the problem, 70% of students were capable to plan the problem-solving, 40% of students were adequate to execute the plan of problem-solving, and 20% students were competent to check the entirety of problem-solving. Keyword: Problem Solving, Story Problems¸ Polya Indicator Abstrak Suatu permasalahan selalu datang setiap harinya yang membutuhkan penyelesaian tepat,cepat tanpa ada kesalahan. Matematika sebagai merupakan mata pelajaran wajib disekolah memiliki kedudukan yang penting bagi kehidupan yakni salah satunya sebagai sarana melatih diri dalam menyelesaikan permasalahan. Permasalahan yang sering mengalami hambatan di kalangan peserta didik adalah rendah nya pemahaman peserta didik dalam menyelesaikan soal matematika bentuk cerita. Penelitian ini bertujuan untuk melihat tingkat kemampuan peserta didik dalam menyelesaikan soal matematika bentuk cerita. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Subjek dalam penelitian ini yakni peserta didik kelas IX SMP Negeri 1 Telagasari berjumlah 30 Peserta didik yang diambil secara Randam. Hasil pengolahan data berdasarkan indikator polya, 23,33% peserta didik memahami masalah, 70% peserta didik mampu merencanakan pemecahan masalah, 40% peserta mampu melaksanakan rencana pemecahan masalah, dan 20% peserta didik mampu melihat kembali kelengkapan pemecahan masalah. Kata Kunci: Pemecahan Masalah, Soal Cerita, Indikator Polya.